Neural Stem Cell Therapy and Rehabilitation in the Central Nervous System: Emerging Partnerships - Ross, Heather H. (Phys Ther, 2016)
The goal of regenerative medicine is to restore function through therapy at levels such as the gene, cell, tissue, or organ. For many disorders, however, regenerative medicine approaches in isolation may not be optimally effective. Rehabilitation is a promising adjunct therapy given the beneficial impact that physical activity and other training modalities can offer. Accordingly, “regenerative rehabilitation” is an emerging concentration of study, with the specific goal of improving positive functional outcomes by enhancing tissue restoration following injury. This article focuses on one emerging example of regenerative rehabilitation—namely, the integration of clinically based protocols with stem cell technologies following central nervous system injury. For the purposes of this review, the state of stem cell technologies for the central nervous system is summarized, and a rationale for a synergistic benefit of carefully orchestrated rehabilitation protocols in conjunction with cellular therapies is provided. An overview of practical steps to increase the involvement of physical therapy in regenerative rehabilitation research also is provided.